First North American record of the Palaearctic rhinophorid Stevenia deceptoria (Loew) (Diptera: Rhinophoridae) - O’hara, James E.; Cerretti, Pierfilippo; Dahlem, Gregory A. (Zootaxa, 2015)
The Rhinophoridae (Diptera) have a cosmopolitan distribution and a known fauna of about 150 species (Cerretti & Pape 2007). So far as known, all species are parasitoids of terrestrial woodlice (sow bugs) of the order Isopoda (Oniscoidea) (Pape 2010). Female rhinophorids lay eggs in the vicinity of potential hosts and the planidial first instars parasitize sow bugs as they pass by (Pape 1998).